A PRELIMINARY STRATEGY TOWARDS SUPPORTING THE AUTOMATION OF SHARIAH-COMPLIANT REQUIREMENTS - Normi Sham Awang Abu Bakar; Azlin Nordin; Madihah Sheikh Abdul Aziz; Norzariyah Yahya; Aminudin Che Ahmad; Mohd Khairul Azmi Hassan (Malaysian Journal of Computing)
Web-based technology offers a wide range of online services in practically every industry, including the medical field. The ISO MS 1900:2014 certification has been awarded to the Sultan Ahmad Shah Medical Centre (SASMEC)@IIUM (Shariah-based Quality Management System). All hospital reporting processes are currently carried out manually using a variety of physical forms, such as the food premise inspection form, the complaint form, and the programme monitoring form to support the implementation and monitoring of the shariah- compliance-related activities. This strategy necessitates a considerable amount of effort, time, and resources to manage these manual activities. These problems have led to insufficient and inefficient planning for auditing and monitoring purposes. This paper proposes the Shariah- Compliant Hospital Reporting System (SC-HRS) to be implemented in SASMEC. The suggested solution will be able to facilitate the Department of Shariah Compliance with a variety of shariah-compliance-related tasks, such as online reporting and monitoring. The ability of this reporting system to manage all reports pertaining to shariah-compliance in a secured database will be advantageous to the department and SASMEC in general.